Establishment of Morphogenic and Regeneration Ability in two Indica Rice Cell Suspension Cultures after Exposure to NaCl (Plant Tissue Culture and Biotechnology, 2010)
An efficient protocol was developed for in vitro morphogenic ability along with plantlet regeneration of two Bangladeshi indica rice varieties (BR24 and BR26) via somatic embryogenesis by applying 50 mM NaCl stress in callus induction and suspension initiation media. Osmotic stress was induced by NaCl (50, 100, 150, 200 and 250 mM) on the cell growth in suspension maintenance media. In viability test stress adapted cells showed 85 - 95% viability up to 200 mM NaCl compared with stress shocked (MS1-50) and control (MS1-0) treatments. Higher stress adapted cells showed growth retardation and the induction of plasmolysis. For both genotypes somatic embryos were obtained in both MS based liquid and semisolid media with or without 50 and 100 mM NaCl. Cell suspension-derived micro-calli were partially desiccated (6 - 12 hr) and subsequently maintained in MS1 callus induction media supplemented with proline (12 mM), ABA (2 mg/l) and 0.6% phytagel in the presence or absence of 50 and 100 mM NaCl. Subsequently, desiccated somatic embryos were transferred in MS based regeneration media with or without 50 and 100 mM NaCl. Proline mediated callus was found to be more effective in embryo differentiation than ABA. Partial desiccation dramatically enhanced callus growth and partially increased regeneration percentage. BR24 showed a better regeneration response producing plantlets in presence of proline in control media while BR26 restored regeneration potential in the presence of ABA and 100 mM NaCl. Plantlets regenerated from salt stressed callus cultures were then grown in compost in a glasshouse and produced normal, fertile plants.  Key words: Indica rice, Cell suspension, Morphogenic, Regeneration D.O.I. 10.3329/ptcb.v19i2.5436 Plant Tissue Cult. & Biotech. 19(2): 185-197, 2009 (December)